Internalization of Qur'anic Character Through The Maghrib Mengaji Program (Case Study of TPQ Baiturrahman, Kuala Enok, Indragiri Hilir, Riau) - Nurlatipah; M Sholih Salimul Uqba; Evy Nur Rohmawaty; Nasrulloh (Lembaga Penelitian Universitas YARSI, 2025)
The objective of this study was to ascertain the implementation of the Maghrib Mengaji program at TPQ Baiturrahman with the aim of instilling Qur'anic character education in children in the Kuala Enok environment. In addition, this study sought to identify the obstacles in the implementation of the Maghrib Mengaji program and to propose solutions to overcome these obstacles. This research employed a descriptive qualitative approach. Data collection techniques included observation and interviews which were then analyzed using techniques from Miles, Huberman and Saldana. The research findings indicate that the Maghrib Mengaji program aims to instill Qur'anic character through in-depth Qur’anic reading, memorization of the Juzz Amma surah, interpretation of Qur’anic verses, hadith, and Arabic aphorisms (mahfuzhat). However, the program encounters challenges due to the large number of students and the limited number of teachers. To overcome these obstacles, it is essential to provide a learning environment that is both engaging and under the guidance of a teacher. The Maghrib Mengaji program plays an essential role in shaping the Qur'anic character of students through guidance, continuous training, and advice in Qur'anic character formation during early childhood.